Exploring the relationship between perceived organizational support and affective commitment among Saudi employees: the mediating effect of organizational trust - Elamin, Abdallah M. (Business: Theory and Practice, 2024)
Despite the acknowledged importance of perceived organizational support (POS), organizational trust (OT), and affective commitment (AC) for favorable organizational outcomes, relatively little is known about the processes that underlie these various associations, especially in Islamic, Arabian Middle Eastern contexts. This study aims to address this gap by exploring the relationships between POS and AC, and testing the mediating effect of OT in the Kingdom of Saudi Arabia (KSA). This study conducted a survey of 347 Saudi employees from a wide range of organizations, occupations, and industries and performed a hierarchical regression analysis. The results provided evidence of the validity of the three relevant constructs (POS, OT, AC) and the generalizability these constructs have outside of North American samples. It also indicated that POS is a significant predictor of OT, and both POS and OT were significant determinants of AC. The study also revealed that OT partially mediates the relationship between POS and AC. The findings contribute to a better understanding of the POS-OT-AC link in the Islamic Arabian context of the KSA. This study is among the first to test the mediating effect of OT on the POS-AC relationship, aiding the understanding of the indirect relationship between POS and AC.